Marketing Plan to Increase Competitive Advantage of MSMEs - Utami, Tri Lestari Wahyuning; Tatik, Tatik; Muttahari, Tiara Firda; Khairunnisa, Adinda Khansa (Asian Journal of Community Services, 2024)
Marketing planning is essential for a company. Effective marketing planning helps MSMEs to be able to target the appropriate market share and have a sustainable competitive advantage related to increasing sales turnover. However, implementing appropriate marketing strategies is still an obstacle for MSMEs. In this case, MSMEs who are members of Genpro DIY Kedu apparently still have problems regarding how to arrange effective marketing plans. Therefore, this community service program aims to provide technical understanding and training in marketing planning for MSMEs. After participating in this program, MSMEs are expected to be able to develop an effective marketing plan to increase sales and their competitiveness.